Optimized PV-coupled battery systems for combining applications: Impact of battery technology and geography. (September 2019) - Pena-Bello, A.; Barbour, E.; Gonzalez, M.C.; Patel, M.K.; Parra, D.
Abstract: Interest in residential batteries to supply photovoltaic (PV) electricity on demand is increasing, however they are not profitable yet. Combining applications has been suggested as a way to increase their attractiveness, but the extent to which this can be achieved, as well as how the different value propositions may affect the optimal battery technology, remain unclear. In this study, we develop an open-source optimization framework to determine the best-suited battery technology depending on the size and the applications combined, including PV self-consumption, demand load-shifting, demand peak shaving and avoidance of PV curtailment. Moreover, we evaluate the impact of the annual demand and electricity prices by applying our method to representative dwellings in Geneva (Switzerland) and Austin (United States). Our results indicate that the combination of applications help batteries to become close to break-even by improving the net present value by up to 66% when compared with batteries performing PV self-consumption only. Interestingly, we find that the best-suited battery technology in Austin is lithium nickel cobalt aluminum oxide (NCA) as for Geneva lithium nickel manganese cobalt oxide (NMC) batteries reach in average a higher net present value than NCA-based batteries. However, NCA-based batteries could be a more promising alternative when applications are combined. Highlights: An open-source model of PV-coupled batteries which supports different technologies and consumer applications is provided. NCA and NMC-based batteries are the best technologies for the Austin and Geneva respectively. The impact of the battery technology choice is more limited than the type of applications which are combined. The combination of applications can residential batteries to reach profitability before 2030.